Palladium-Catalyzed C(sp2)−H Olefination/Annulation Cascades of Aryl Carboxamides Assisted by N,S-Bidentate Auxiliary - Li, Ling; Zhang, Xing-Guo; Zhang, Xiao-Hong (Synthesis, 2019)
A palladium(II)-catalyzed olefination/annulation of aryl carboxamides, assisted by an N, S-bidentate auxiliary, with methyl acrylate is described. Various carboxamides with a number of functional groups were compatible with this reaction to afford, regioselectively and in moderate yield, (E)-3-methyleneisoindolin-1-one derivatives bearing an alkyl(aryl)thio group.
Keywords: palladium(II)-catalyzed; olefination; annulation; carboxamides; N,S-bidentate directing group; isoindoles